Factors Associated with Risky Sexual Behaviour among Junior High School Adolescents in Lampung Province in 2024 - Shintani, Clara; Muhani, Nova; Aryawati, Wayan; Febriani, Christin Angelina (Jurnal Dunia Kesmas, 2025)
According to the World Health Organization, adolescents aged 10-19 years make up more than 16% of the global population and have a significant impact on achieving the Sustainable Development Goals by 2030. The purpose of this study was to determine the factors associated with sexual behaviour of junior high school adolescents in Lampung Province. This study used a cross sectional design. With the sampling process, namely Purposive Random Sampling, the sample size was 132 respondents using research instrument data, namely questionnaires distributed in several forms. The results of this study are of the five variables taken (place of residence, ims & hiv knowledge, use of information and communication technology, the role of parents, the role of peers) found that the factors associated with sexual behaviour are the use of information and communication technology p-value 0.014. Multivariate modelling showed that the use of information and communication technology was the dominant factor with p-value 0.027 and OR 3.133 (95%CI 1.136-8.637) so that it was found that the use of technology and communication was the most influential factor on sexual behaviour in junior high school adolescents. Conclusion The use of information and communication technology increases the risk 3.1 times to perform sexual behaviour or not to perform premarital sexual behaviour with the suggestion that it is necessary to provide education that is more concerned and supervises adolescents in using information and communication technology.